Antioxidant activities of Ananas comosus peel extracts: a review on in vitro and in vivo approaches / Erliana Safri … [et al.] - Safri, Erliana; Haron, Norhisham; Abdullah, Anas; Mohamed, Emida; Camalxaman, Siti Nazrina; Ramlee @ Rambely, Azlin Sham (Faculty of Applied Sciences, 2023)
Peel of Ananas comosus (pineapple) is a valuable waste as it contains antioxidant compounds that exhibit radical scavenging activity, which is capable of preventing oxidative stress, a cause of the development of chronic diseases in humans. Various in vitro and in vivo methods have been previously applied in studies investigating pineapple peel extract's antioxidant properties. However, different results were reported throughout each study, and limited papers discussed on the antioxidant properties of the peel extract. Therefore, this review summarized the antioxidant activities of A. comosus peel extract through different types of in vitro and in vivo models. The result showed that pineapple peel extracts were able to scavenge different types of free radicals through in vitro models as the antioxidant present neutralized the radicals by hydrogen electron transfer (HAT), single electron transfer (SET), or mixed of both reactions. Findings from in vivo models showed antioxidative effects as they regulated the level of the enzymes involved in combating free radicals and attenuated lipid peroxidation. The evidence reviewed here suggested that the peel of A. comosus could be a source of natural antioxidants. Thus, more studies are required in the future to evaluate its ability to scavenge free radicals effectively.